High pressure densities and derived thermodynamic properties for the (n-heptane + n-octane + ethanol) ternary system. (June 2017) - Abdussalam, Ali A.; Radović, Ivona R.; Ivaniš, Gorica R.; Lj. Kijevčanin, Mirjana
Highlights: Densities of n -heptane +  n -octane + ethanol system at high pressures. Correlation of the high pressure densities using the modified Tammann-Tait equation. Excess molar volume, isothermal compressibility and isobaric thermal expansion coefficient calculations. Positive excess molar volumes over the entire ternary area. Strong influence of pressure and temperature on non ideal behaviour of the mixture. Abstract: The density of the ternary system ( n -heptane +  n -octane + ethanol) at temperatures from (293.15 to 373.15) K and at pressures from (0.1 to 40) MPa was experimentally determined at twelve compositions and the results are presented here. Measurements were performed using high pressure U-tube cell DMA HP coupled with DMA 5000 vibrating density meter. To fit the experimental density values the modified Tammann-Tait equation was applied. Excess molar volumes were also calculated at all pressures and temperatures in order to explain to what extent the investigated mixtures deviate from ideal behaviour. Moreover, the influence of pressure and temperature on density was studied by calculating isothermal compressibility and isobaric thermal expansion coefficient. It was found that non-ideal behaviour of the ternary mixture is strongly influenced by pressure and temperature conditions.